ANALISIS YURIDIS LEGALITAS KEPEMILIKAN HAK ATAS TANAH DI PULAU REMPANG, KEPULAUAN RIAU - Nova Elena; Aartje Tehupeiory; Chris Anggi Natalia Berutu; I Dewa Ayu Widyani (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
This research focuses on the government's plan to develop Rempang Island as an industrial and tourism area through the "Rempang Eco City" project. In this case, the community rejected the existence of the plan because the community considered that there was no certainty for their lives if the land was relocated to be used as an industrial area. The problem in writing this article is only limited to discussing the legality of land rights ownership on Rempang Island, Riau Islands. The writing of this article uses normative legal research methods. This is inseparable from the existing laws and regulations regarding the ownership of land rights regulated in the provisions of the 1945 Constitution, UUPA Number 5 of 1960, Regulation of the Minister of State for Agrarian Affairs/Head of the National Land Agency Number 5 of 1999 and Law Number 39 of 1999. The results of this study show that there is still uncertainty and concern, especially legal certainty for the people on Rempang Island. The planning carried out by the government for the community has also not been maximized. Therefore, it is necessary to have an intensive and inclusive dialogue between all parties to build mutual trust and understanding which is done with the involvement and participation of the community.